Effect of Different Rheumatoid Arthritis Medicines on the Disease Activity Score (DAS) 28 in the Patients with RA Suffering from Bacterial Urinary Tract Infection. (World Journal of Experimental Biosciences, 2022)
Rheumatoid arthritis (RA) is one of the most impact autoimmune diseases in society, as it affects the movement and work of people. There are different types of medications given to patients with RA. The current study aims to fill the knowledge gap related to the effect of urinary tract infection (UTI) caused by bacterial pathogens in people with RA who have taken different types of medications on the activity of the disease in terms of disease activity score (DAS) 28. In the present study, The 100 cohorts included 30 healthy control volunteers and 70 RA patients divided into two groups, The first group contained 41 patients (24 female and 7 male) with RA and UTI; the second group, 29 patients suffering from RA (24 female and 5 male) without suffering from UTI. The study showed that there is no change in the level of disease activity DAS28 in the patients with RA getting different RA medicines (1. Enbrel and Methotrexate, 2. Enbrel, 3. Methotrexate, 4. Humira and methotrexate, 4. Rituximab) and their urinary tract infected with different bacteria as compared with DAS28 of RA patients using above medicine and did not suffer bacterial UTI. (P>0.05). No effect of the type of medicine on the DAS28 in each patient group. It was concluded for the first time that the RA medicines do not affect the activity of RA (DAS28) in patients with RA and suffering from UTI or not suffering from UTI.